Feminist frontiers (McGraw Hill, 2009)
The most widely used anthology of feminist writings and the first to incorporate issues of sexual identity and sexual diversity, Feminist Frontiers has stood the test of time. With both classic and contemporary readings on cutting-edge topics that cut across disciplinary and generational lines, this text presents the full diversity of women's lives, exploring commonalities as well as interconnected differences. Feminist Frontiers offers analyses of the causes and consequences of gender inequality in interaction with class, race, ethnicity, sexuality, ability, and nationality. This anthology also introduces students to feminist theory and methodology. This edition maintains consistent coverage of diverse ethnicities and a global perspective, with greater attention to transgender issues and disability.